2013
DOI: 10.1055/s-0032-1331257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Marathon Running on Cardiac Markers and Endothelin-1 in EIH Athletes

Abstract: The aim of the present study was to determine the changes in cardiac makers and endothelin-1 (ET-1) in marathoners with exercise induced hypertension compared to normotensive controls before and after running a marathon. Among a total of 70 volunteers, 10 marathoners with systolic blood pressure (SBP) greater than 210 mmHg during a treadmill exercise stress test were selected as an exercise-induced hypertension group (EIH) and 10 marathoners with normal SBP were selected as a control group (CON). Blood was col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…However, cTnI and NT-proBNP were recently reported to be increased in runners with exercise-induced hypertension in marathons and ultramarathons. 16,17 These data, in combination with the results shown in the present study, support the following hypothesis: middle-aged marathon runners with potential ischemic cardiovascular disease and excessive increases in BP may undergo increased myocardial ischemia caused by increased oxygen demand of the myocardia, which, in turn, induces cardiac events such as arrhythmia. In this study, 13 (32.5%) of 40 runners exhibited exercise-induced hypertension.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, cTnI and NT-proBNP were recently reported to be increased in runners with exercise-induced hypertension in marathons and ultramarathons. 16,17 These data, in combination with the results shown in the present study, support the following hypothesis: middle-aged marathon runners with potential ischemic cardiovascular disease and excessive increases in BP may undergo increased myocardial ischemia caused by increased oxygen demand of the myocardia, which, in turn, induces cardiac events such as arrhythmia. In this study, 13 (32.5%) of 40 runners exhibited exercise-induced hypertension.…”
Section: Discussionsupporting
confidence: 88%
“…The induction of cardiac troponin after excessive exercise has been reported to be primarily affected by exercise intensity, whereas the induction of N-terminal pro-B-type natriuretic peptide (NT-proBNP) is related to exercise duration. 14,15 According to recent reports, cardiac troponin I (cTnI), NT-proBNP, and endothelin-1 (ET-1) are induced to higher levels in marathon runners with exercise-induced high BP, 16 whereas NT-proBNP, creatine kinase (CK), and high-sensitivity Creactive protein (hs-CRP) are induced to higher levels in 100-km ultramarathon runners with exercise-induced high BP. 17 Previous studies were conducted with only a small number of cases and lack of variability of exerciseinduced hypertension.…”
mentioning
confidence: 99%
“…3 ). Levels of cTnI can be increased by extreme exercise such as a marathon or a 100-km ultramarathon [ 1 , 12 , 24 , 25 ]. They can even exceed the URL.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that expression levels of cardiac markers in exercise-induced hypertension (EIH) runners are higher than those in ultramarathon runners with normal response [ 11 ]. EIH runners have been reported to have higher myocardial load and increased skeletal muscle damage during marathon [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports show that the incidence of exercise-induced hypertension (EIH) is high [ 7 ] among long-distance runners and that runners with EIH show a greater elevation of cardiac troponin I, a marker for myocardial injury, and N-terminal fragment of the prohormone brain-type natriuretic peptide, a marker for myocardial volume-pressure, than normal runners during a marathon or ultramarathon, [ 8 , 9 ] raising concerns for the risk of cardiac events during exercise. EIH is defined as a normal resting blood pressure (BP) of <140/80 mm Hg with a maximum systolic BP (SBP) ≥210 mm Hg.…”
Section: Introductionmentioning
confidence: 99%